Plasma metabolomic analysis reveals the therapeutic effects of Jiashen tablets on heart failure - Miao, Xinglong; Chen, Jiaping; Su, Yangyan; Luo, Jiayi; He, Yi; Ma, Jiang; He, Xin (Frontiers in Cardiovascular Medicine, 2022)
Background Heart failure is a chronic progressive condition that significantly affects the quality of life of patients with high hospitalization and mortality rates. Jiashen tablets (JST), a Chinese herbal formula, have been reported to be an effective treatment against heart failure, however the underlying mechanisms remain obscure. This study was designed to determine the effect of JST on the treatment of heart failure and delineate the underlying mechanisms by an untargeted metabolomics approach. Materials and methods The chronic heart failure model was established by the permanent ligation of the left anterior descending coronary artery in rats. The cardiac functions of rats, including left ventricular ejection fraction (LVEF) and fractional shortening (LVFS), left ventricular internal diameter end diastole (LVIDd) and end systole (LVIDs), and interventricular septum thickness in diastole (IVSd) and in systole (IVSs), were measured by echocardiography. Biochemical analysis and histopathological examination were also performed to evaluate therapeutic effects of JST for treating heart failure. UHPLC-QTOF-MS/MS coupled with multivariate statistical analyses were applied for plasma metabolic profiling to identify biomarkers and potential mechanisms of JST in the treatment of heart failure. Results Jiashen tablets could improve the cardiac function of heart failure rats and thus ameliorate heart failure via enhancing rat LVEF and LVFS and decreasing LVIDd, LVIDs, IVSd, and IVSs. Results of biochemical analysis and histopathological examination revealed that JST could reduce the serum lactate dehydrogenase (LDH) activity and the level of NT-pro BNP, markers of heart failure and myocardial damage, and inhibit myocardial fibrosis. Furthermore, in metabolomics analysis, a total of 210 metabolites with significant differences were identified between heart failure rats and normal rats, among which 29 metabolites were significantly restored after JST treatment. These metabolites were primarily involved in tryptophan metabolism, branched-chain amino acid metabolism, fatty acids β-oxidation, and glycerophospholipid metabolism. Conclusion The present study illustrated the therapeutic effect of JST for the treatment of heart failure and delineated the underlying mechanisms mainly relating to the regulation of amino acid metabolism and lipid metabolism in heart failure rats.